(3GdaUhd (B_ (3GdeONd aj GdeLSWis - (3CHh GdYHGS CMeO Hf eMeO Hf cKjQ GdaQZGfi,J (B240 (3g` s
(3ChdgG (B:s
(3gPG cJGH Cdag ai LhGeY Yde GdfLhe hCUhd GdMQcGJ GdSeGhjI GdaUd GdChd ai Sfi GdYQH hGdYLe s
(3BNQgG (B:s
(3abO HjfG cSha GdTeS hGdbeQ eG ajg caGjI hZfi HYhf Gddg Je GdcJGH GdKdGKhf aUdkG HJeGegG s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfis
(3ai GdeYgO fSNI CNQi HYfhGf (B: (3CUhd Yde GdfLhe HQbe (B13 (3adc hai fSN CNQi HYfhGf (B: (3LhGeY Yde GdfLhe hCUhd GdMQcGJ GdSeGhjI hCNQi HYfhGf GdeONd Edi Yde GdgjFIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B249 ; (3HQhcdeGf edMb (B- (3GdLRA (B1 - (3U (B392 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B2 - (3U (B189 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdadcs